2015
DOI: 10.1088/1674-4527/15/7/001
|View full text |Cite
|
Sign up to set email alerts
|

The broadband spectral energy distributions of SDSS blazars

Abstract: We compiled the radio, optical, and X-ray data of blazars from the Sloan Digital Sky Survey (SDSS) database, and presented the distribution of luminosities and broad band spectral indices. The distribution of luminosities shows that the averaged luminosity of flat-spectral radio quasars (FSRQs) is larger than that of BL Lacs objects. On the other hand, the broad band spectral energy distribution reveals that FSRQs and low energy peaked BL Lac objects (LBLs) objects have similar spectral properties, but high en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…We also found that the slopes of correlations for TeV HSP BLs are similar to those for non-TeV HSP BLs, and the log νL γ vs log νL R correlation is strongest. The strong γray vs radio correlation was also discussed by other authors (Dondi & Ghisellini 1995;Muecke et al 1997;Xie et al 1997;Zhou et al 1997;Fan et al 1998Fan et al , 2012Fan et al , 2015Fan et al , 2016Cheng et al 2000;Yang & Fan 2005;Giroletti et al 2010Giroletti et al , 2012Pushkarev et al 2010;Linford et al 2011;Yang et al 2012bYang et al ,a, 2014Li et al 2015).…”
Section: Correlationssupporting
confidence: 57%
“…We also found that the slopes of correlations for TeV HSP BLs are similar to those for non-TeV HSP BLs, and the log νL γ vs log νL R correlation is strongest. The strong γray vs radio correlation was also discussed by other authors (Dondi & Ghisellini 1995;Muecke et al 1997;Xie et al 1997;Zhou et al 1997;Fan et al 1998Fan et al , 2012Fan et al , 2015Fan et al , 2016Cheng et al 2000;Yang & Fan 2005;Giroletti et al 2010Giroletti et al , 2012Pushkarev et al 2010;Linford et al 2011;Yang et al 2012bYang et al ,a, 2014Li et al 2015).…”
Section: Correlationssupporting
confidence: 57%
“…Odo and Aroh 2020). Li et al (2015) earlier argued that the αro − z correlation using SDSS data provides more evidence for the unified scheme as proposed by Fossati et al (1998).…”
Section: Discussionmentioning
confidence: 91%
“…Other possible effects that could affect our intrinsic quasar photometry model would be systematic variations in the emission lines, e.g., the Baldwin effect (Baldwin 1977), blazars with no apparent emission lines, or quasars with abnormal spectral shapes (Meusinger et al 2012). However, as blazars and quasars with abnormal spectral shapes contribute very little to the overall population of quasars (Meusinger et al 2012;Li et al 2015), we have neglected the contribution of these in order to keep the model as simple as possible.…”
Section: Simulating Quasar Photometrymentioning
confidence: 99%